DEVELOPMENT OF AN EFFICIENT MECHANISM OF SERVICE TO THE ELECTRICITY SUPPLY SYSTEM (Web of Teachers: Inderscience Research, 2024)
This article deals with the principal mechanisms of servicing oil transformers that serve the population. In this, the principles of easy, safe and economical servicing of oil transformers are given.